Vacuolar H+-Pyrophosphatase AVP1 is Involved in Amine Fungicide Tolerance in Arabidopsis thaliana and Provides Tridemorph Resistance in Yeast - Hernández, Agustín; Herrera-Palau, Rosana; Madroñal, Juan M.; Albi, Tomás; López-Lluch, Guillermo; Perez-Castiñeira, José R.; Navas, Plácido; Valverde, Federico; Serrano, Aurelio (Frontiers in Plant Science, 2016)
Amine fungicides are widely used as crop protectants. Their success is believed to be related to their ability to inhibit postlanosterol sterol biosynthesis in fungi, in particular sterol-Δ8,Δ7-isomerases and sterol-Δ14-reductases, with a concomitant accumulation of toxic abnormal sterols. However, their actual cellular effects and mechanisms of death induction are still poorly understood. Paradoxically, plants exhibit a natural resistance to amine fungicides although they have similar enzymes in postcicloartenol sterol biosynthesis that are also susceptible to fungicide inhibition. A major difference in vacuolar ion homeostasis between plants and fungi is the presence of a dual set of primary proton pumps in the former (V-ATPase and H+-pyrophosphatase), but only the V-ATPase in the latter. Abnormal sterols affect the proton-pumping capacity of V-ATPases in fungi and this has been proposed as a major determinant in fungicide action. Using Saccharomyces cerevisiae as a model fungus, we provide evidence that amine fungicide treatment induced cell death by apoptosis. Cell death was concomitant with impaired H+-pumping capacity in vacuole vesicles and dependent on vacuolar proteases. Also, the heterologous expression of the Arabidopsis thaliana main H+-pyrophosphatase (AVP1) at the fungal vacuolar membrane reduced apoptosis levels in yeast and increased resistance to amine fungicides. Consistently, A. thaliana avp1 mutant seedlings showed increased susceptibility to this amine fungicide, particularly at the level of root development. This is in agreement with AVP1 being nearly the sole H+-pyrophosphatase gene expressed at the root elongation zones. All in all, the present data suggest that H+-pyrophosphatases are major determinants of plant tolerance to amine fungicides.